TiO2 Mesocrystals Processed at Low Temperature as the Electron‐Transport Material in Perovskite Solar Cells. Issue 19 (20th August 2020) - Guo, Minghuang; Shen, Deli; Li, Yafeng; Akram, Muhammad Aftab; Wei, Mingdeng
Abstract: TiO2 is the most widely used material for preparing the electron‐transporting layer (ETL) in perovskite solar cells (PSCs). However, it requires a high‐temperature sintering process. Moreover, the intrinsic defects and low electron mobility of TiO2 ETLs cause instability and hysteresis effects in PSCs. In this study, a mesoporous film composed of anatase TiO2 mesocrystals was facilely fabricated by a low‐temperature route and then used as an ETL in PSCs for the first time. A satisfactory efficiency of 20.26 % can be achieved through delicate control of the entire device fabrication procedure. The optimal device, with an area of 1 cm 2, achieves an efficiency of 17.07 %. In comparison to the common TiO2 ETLs, those composed of TiO2 mesocrystals show the enhanced electron extraction and suppression of charge accumulation at the perovskite/ETL interface, resulting in improved photovoltaic performance and reduced hysteresis. Abstract : Electron transport material : Anatase TiO2 mesocrystals are used as an electron‐transport layer in mesoporous perovskite solar cells (PSCs) at low temperature proceess The photovoltaic efficiency of PSCs is significantly enhanced, which might be attributed to higher electron transport capacity of TiO2 mesocrystals and superior surface contact with the perovskite and ETLs.